Persepsi Mahasiswa terhadap Perkuliahan Daring Matakuliah Metode Numerik - Ardiansyah, M. (Asatiza: Jurnal Pendidikan, 2021)
This study was to explore informatics students' perceptions about the implementation of online lectures using the google form application. This was a descriptive case study involving 150 students of the 3rd-semester of the informatics program Universitas Indraprasta PGRI Jakarta Academic Year 2019/2020. The results were obtained through a questionnaire, interviews, and observations. The data analysis focused on student interpretation and reaction. The results of the questionnaire showed that 88% of students have positive statements, while another 12% were negative. The data also revealed that average students give a positive response to online lectures and they can use supporting applications of google form, they agreed that online lectures were very fun and effective during a stable internet connection. However, students needed to have face to face lectures to ensure their understanding.